Development of soil formation corresponding to cyclic stress - derived shear strain function based on stratum index factor - Abdul, A.H. (GEOMATE International Society, 2016)
Historically shear strain function and complex shear modulus based on geophysical methods were based on empirical relationship between Seismic Cone Penetration Test (SCPT) and Cone Penetration Test (CPT) method. New geological concept namely CPI model have been developed and applied in mathematical and engineering strains to study shear strain function. Modeling of the mathematical shear strain is done by halving the stratum index factor (SIF). The different types of responses of CPI model are discussed and classified based on numerical methods using degree of settlement and degree of consolidation. The results show that shear strain amplitude or mathematical shear strain is constant by using the modified CPI method where mathematical shear strain indicated is half of the stratum index factor and engineering shear strain indicated is equal to the stratum index factor. The other major al area. Last major finding involves the cyclic variation of Poisson Ratio which indicates the anisotropic properties of soft cohesive soil. Â© 2015, Int. J. of GEOMATE. All rights reserved.